Phakic Posterior Chamber Intraocular Lens with a Central Hole in Treating Patients with Moderate to High Myopia: A Meta-Analysis - Ying Tang; Jian Ye (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of phakic posterior chamber intraocular lens with a central hole (ICL V4c) in treating patients with moderate to high myopia. Methods. PubMed, Embase, Cochrane Library, Clinical Trial, China Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), and China Science Periodical Database (CSPD) were searched online. The search included publications from the building of the library until December 2018. All randomized controlled trials containing moderate to high myopia treated by phakic posterior chamber intraocular lens with a central hole were collected. Literature search, screening literature, data extraction, and quality evaluation were independently performed by two reviewers. Meta-analysis was performed using RevMan 5.3 software. Results. Meta-analysis results based on five randomized controlled trials showed that ICL V4c and ICL without a central hole had similar UCVA results (SMD = 0.08, 95% CI (−0.71, 0.88), P=0.84), SE (SMD = −0.18, 95% CI (−0.52, 0.15), P=0.29), BCVA (SMD = −0.27, 95% CI (−0.93, 0.40), P=0.43), and IOP (SMD = 0.03, 95% CI (−0.24, 0.30), P=0.84), and the difference was not statistically significant. In addition, no complications that could jeopardize vision occurred. Conclusions. Implanting ICL V4c in patients with moderate to high myopia is safe and effective.